2002
DOI: 10.1007/s00104-001-0385-1
|View full text |Cite
|
Sign up to set email alerts
|

Nachweis parodontal pathogener Mikroorganismen in atheromatösen Plaques Vorläufige Ergebnisse

Abstract: These findings indicate that periodontal pathogens are present in atherosclerotic plaques, where they may play a role in the development and progression of atherosclerosis leading to coronary vascular disease and other clinical sequelae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 41 publications
0
1
0
1
Order By: Relevance
“…Diversos estudos apontam que, ao conseguirem acesso à corrente sanguínea, microorganismos que deveriam se restringir à cavidade oral, podem afetar as diversas áreas do organismo, promovendo o início de processos inflamatórios sistêmicos e mecanismos pró-trombólicos. O endotélio vascular mostra-se como uma destas áreas afetadas, onde se dissemina um processo inflamatório que associado a quadros de hiperlipidemia coexistentes, promovem a situação perfeita para o desenvolvimento da aterosclerose e posteriores manifestações patológicas decorrentes da mesma (Mastragelopulos et al, 2002;Pires et al, 2013).…”
Section: Discussionunclassified
“…Diversos estudos apontam que, ao conseguirem acesso à corrente sanguínea, microorganismos que deveriam se restringir à cavidade oral, podem afetar as diversas áreas do organismo, promovendo o início de processos inflamatórios sistêmicos e mecanismos pró-trombólicos. O endotélio vascular mostra-se como uma destas áreas afetadas, onde se dissemina um processo inflamatório que associado a quadros de hiperlipidemia coexistentes, promovem a situação perfeita para o desenvolvimento da aterosclerose e posteriores manifestações patológicas decorrentes da mesma (Mastragelopulos et al, 2002;Pires et al, 2013).…”
Section: Discussionunclassified
“…Several studies using targeted techniques were able to identify oral microorganisms, especially red complex pathogens, in coronary samples. T. forsythia was found in 3.7–61.9% of samples [28] [31] . Other studies identified P. gingivalis in atheromatous plaques, either alone [32] or in concomitant colonization with P. intermedia , T. forsythia and A. actinomycetemcomitans [29] , [33] , in 4.17 to 85% of samples [34] , [35] .…”
Section: Discussionmentioning
confidence: 99%